Risk of Diabetes among Patients Receiving Primary Androgen Deprivation Therapy for Clinically Localized Prostate Cancer - Tsai, Huei-Ting (J Urol, 2014)
PURPOSE: Androgen deprivation therapy may increase diabetes risk. As the benefits of primary androgen deprivation therapy for localized prostate cancer are controversial, and most prostate cancer survivors are of advanced age with comorbidities, it is important to determine if primary androgen deprivation therapy increases the risk of diabetes and to determine the susceptibility factors. MATERIALS AND METHODS: We conducted a retrospective cohort study of 12,191 men diagnosed with incident localized prostate cancer during 1995 to 2008, age 35 to 100 years, and without diabetes or receipt of prostatectomy or radiation 1 year after diagnosis. Patients were enrolled in 1 of 3 managed health plans and followed through 2010. Primary androgen deprivation therapy was defined as androgen deprivation therapy within 1 year after diagnosis. Incident diabetes was ascertained using inpatient and outpatient diagnosis codes, diabetes medications and hemoglobin A1c values. We estimated primary androgen deprivation therapy associated diabetes risk using Cox proportional hazard models in conventional and propensity score analyses. RESULTS: Diabetes developed in 1,203 (9.9%) patients during followup (median 4.8 years) with incidence rates of 2.5 and 1.6 events per 100 person-years in the primary androgen deprivation therapy and nonprimary androgen deprivation therapy groups, respectively. Primary androgen deprivation therapy was associated with a 1.61-fold increased diabetes risk (95% CI 1.38–1.88). The number needed to harm was 29. The association was stronger in men age 70 or younger than in older men (HR 2.25 vs 1.40, p value for interaction = 0.008). CONCLUSIONS: Primary androgen deprivation therapy may increase diabetes risk by 60% and should be used with caution when managing localized prostate cancer. Because of the consistent association between androgen deprivation therapy and greater diabetes risk across disease states, we recommend routine screening and lifestyle interventions to reduce the risk of diabetes in men receiving androgen deprivation therapy.